(untitled) (Research, Society and Development, 2023)
Gestational syphilis (GS) is a worrying infectious disease that can be transmitted from the mother to the fetus, causing serious complications for the health of the pregnant woman and the newborn. This article aims to analyze the epidemiology of gestational syphilis in Northeast Brazil, focusing on data collected between 2018 and 2021. Using secondary information from the Notifiable Diseases Information System (SINAN), aspects such as age group, race, education level, gestational age at diagnosis, clinical classification of the disease and treatment of pregnant women with syphilis were examined. The results point to a significant incidence of the disease, with emphasis on the prevalence among young women with low education. Late identification of gestational syphilis is also a relevant concern, highlighting the urgent need to improve access to prenatal care and implement more effective screening for the disease. Although penicillin treatment is widely used, the persistence of challenges in regions with socioeconomic deficits requires a more comprehensive approach. This analysis highlights the importance of effective public policies to address gestational syphilis, seeking to ensure an integrated approach to protect maternal and child health in the Brazilian Northeast region. The study emphasizes the importance of investing in health education programs, increasing awareness about prevention, prenatal care and adequate treatment. In addition, it emphasizes the need for greater attention to the most vulnerable populations and targeted actions to reduce social inequalities and unequal access to health services.